(untitled) (Quinto Sol, 2014)
During the last decades of the nineteenth-century, new products that were traditionally not considered for export, appeared -wheat, corn, linseed, frozen beef and lamb-. As a result, goods that were sold abroad after the Independence started a declination process. Nevertheless, we must point out to that some of them declined in absolute terms -salt meat, tallow and other cattle products-, while another group diminished it participation relatively in the whole export value -wool and hides-. In this paper, we propose the reconstruction of the trajectory of the dirty wool and different types of hides between 1890 and 1913. For such a purpose, we used a new trade series created by us, based on the correction of the official value. For the first time in the historiography the products are related to the destinies. Besides, as a complement, we work with unpublished diplomatic sources as Serie Diplomática y Consular from the Foreign Relations Ministry Archive.